Study on $H_3^+$ Formation by Synchrotron Radiation (Journal of Atomic and Molecular Sciences, 2014)
A molecular beam experiment on the formation of $H^+_3$ has been carriedout by using tunable vacuum ultraviolet (VUV) synchrotron radiation. Reflectrontime-of-flight mass spectrometer is applied to detect the signal of $H^+_3.$ The ionizationenergy (IE) of $H_2$ and the appearance energy (AE) of $H^+_3$ are determined to be15.41 eV and 14.61 eV, respectively, by measurements of photoionization efficiency(PIE) curves. Additionally, two most likely $H^+_3$ formation ways, $(H_2)2→ H^3_+ +H$ and $(H_2)_3 → H^+_3 +H+H_2,$ are discussed by ab initio calculations at CCSD(T) and MP2 levelwith aug-cc-pVQZ basis set and compared with the experimental result. The optimizedgeometries of species involved in the dissociative photoionization channels arealso determined at MP2/aug-cc-pVQZ level.
Keywords: $H^+_3$; photoionization; synchrotron radiation; ab initio calculation.